The Role of the Cooperative SME and Trade Service in Monitoring the Relocation Policy at the Food Court in Tegal City - Chaisel Akhrennesta; Sri Sutjiatmi; Akhmad Habibullah (Universitas Muhammadiyah Gorontalo, 2026)
The existence of the informal sector, especially street vendors, contributes significantly to employment in Indonesia and is an integral part of urban socio-economic dynamics. However, their presence often leads to relocation policies aimed at organizing urban spatial planning, as seen in Tegal City on January 18, 2025, which involved 124 vendors from 3 main roads. However, its implementation has caused various problems, such as a decrease in turnover of up to 80%, the selection of less strategic locations, and social conflict. This study aims to describe the role of the Cooperatives, SMEs, and Trade Office in overseeing the relocation policy from the proposal stage to implementation. The research method uses a descriptive qualitative approach from primary data through structured interviews with service members, field observations, documentation studies, and strengthened secondary data from scientific journals, Regional Regulations, Theses, and online news publications, which are then analyzed thematically using NVivo 12 Pro. The results show that the Cooperatives, SMEs, and Trade Office play the most dominant role as the main coordinator. Their involvement is reflected from the policy proposal stage, data collection, socialization, music entertainment organizers, aspiration absorption, provision and management of facilities, the formation of E-Retribution, as well as participating in collaboration, coordination, and evaluation with other related agencies. Although the institutional role is well implemented according to planning procedures and mechanisms, these achievements have not been fully commensurate with improvements in the economic welfare of street vendors in the food court. This study identifies the need for further studies that focus on the impact of relocation from the vendors' perspective.